Ga-doped IZO films obtained by magnetron sputtering as transparent conductors for visible and solar applications. Issue 5 (1st April 2019) - Solís-Cortés, D.; Navarrete-Astorga, E.; Costa-Krämer, J.L.; Salguero-Fernandez, J.; Schrebler, R.; Leinen, D.; Dalchiele, E.A.; Ramos-Barrado, J.R.; Martín, F.
Abstract: C-axis textured thin films of gallium-doped indium zinc oxide (GIZO) with a 2% ratio of Ga/Zn, were obtained via RF-magnetron sputtering with high transparency and electrical conductivity. A Box-Behnken response surface design was used to evaluate the effects of the deposition parameters (In2 O3 target power, deposition time, and substrate temperature) on the chemical composition, optical, electrical, and structural properties of the GIZO films. The optical constants and the electrical properties were obtained using optical models. The GIZO stoichiometry, and therefore the In/Zn atomic ratio, affected the crystallinity, crystalline parameters, band gap, and charge carrier mobility of the GIZO films. The charge carrier density was related to the change in the crystalline parameters of the hexagonal structure and the In/Zn atomic ratio. The best electrical conductivity values (1.75 × 10 3 Ω −1 cm −1 ) were obtained for GIZO films with In/Zn ratio ≥ 1. Several figures of merit (FOM) defined for the visible and solar regions were comparatively used to select the optimal In/Zn atomic ratio that provided the best balance between the conductivity and the transparency. The optimal In/Zn ratio was in a range of 0.85–0.90 for the GIZO films. Graphical abstract: fx1 Highlights: A Box-Behnken experimental design was used in this study. The relationship between GIZO stoichiometry and the film properties were established. New figures of merit were proposed for the visible and solar regions. In/Zn ratio for a good compromise between conductivity and transparency was found.